IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR (SD) MUHAMMADIYAH METRO PUSAT - Noormawanti Noormawanti (Universitas Muhammadiyah Metro, 2018)
This study discusses the Implementation of Islamic Education Learning. The focus of this study is about: 1) How is the planning, implementation and evaluation of the implementation of learning in Islamic Religious Education at the Muhammadiyah Metro Central Elementary School; 2) What are the supporting and inhibiting factors in the implementation of learning Islamic Education at the Muhammadiyah Metro Central Elementary School. The purpose of this study is to describe: Implementation of Islamic Education Learning in the Muhammadiyah Metro Central Elementary School.The design of this study is to use a qualitative approach with a descriptive research model. So that this research is a qualitative descriptive study. The data collection technique uses observation and interview methods. To make it easier to explain the data, categorization and organization of data is done with a coding system. The research informants were obtained by snowball sampling technique, then testing the validity of the data was done using the triangulation method. In data processing and data analysis carried out during and after conducting research.The results showed that the Implementation of Islamic Education Learning in Muhammadiyah Metro Pusat Elementary School (SD) in the planning process was realized in a Learning Implementation Plan (RPP), which was given a special time by the school to prepare learning tools which included: syllabus formulation, educational calendar , annual programs, semester programs, teaching materials up to remedial activities and endorsed by the school supervision team. In the implementation of Islamic Education Learning in SD Muhammadiyah Metro the Center for Islamic Education Teachers refers to one component of the learning strategy, namely the component of the learning method. The method used by Islamic Education Teachers at Elementary School Muhammadiyah Metro Pusat is the lecture method, discussion method, training method and demonstration method. Evaluations used include: 1) UTS (Semster Middle Examination), 2) Semester Exams, 3) Practice Exams. It is also influenced by supporting and inhibiting factors. Supporting factors include: adequate school infrastructure, professional teachers, character development activities, while the inhibiting factors are limited learning resources and low student motivation.